Chemical control of Lecanium persicae ( Homoptera-Coccidae) - Oliveira, Alda Maria de; Romani, Lucindo Baptista (Pesquisa Agropecuaria Brasileira, 2014)
Lecanium persicae (Fabr. 1776) was controlled with foliar spray application of five insecticides applied to Vitis vinifera (L.) during the spring of 1970, in Bento Gonçalves, State of Rio Grande do Sul, Brazil. The insecticides evalueted in field experiment to control the insect were Super Rhodiatox 60, Folidol oil, Metasystox (i), Ekatin F and Triona B. Three applications were made at approximately 25 days intervals from the beginning of October to December. Use of the insecticides resulted in effective control for the infestation level of 5 scales/leave. Data on biology of the scale were made.